Salsa in Salzburg Gustavo Dudamel conducts the Simón Bolívar Youth Orchestra - Beethoven, Ludwig van 1770-1827; Mussorgsky, Modest Petrovich 1839-1881 (Unitel Productions Inc., 2008)
Marta Argerich, the Capuçon brothers, Gustavo Dudamel and the Simón Bolívar Youth Orchestra unite for an extraordinary concert in Salzburg. Under the heading "Party in the Felsenreitschule," the Munich daily Münchner Merkur boldly proclaimed: "Venezuela's Simón Bolívar Youth Orchestra guests at the Salzburg Festival -- and delivers the biggest audience hit of the summer." Two days after the concert reviewed by the Merkur, the ensemble united its massive forces once again for a spectacular concert in the Grosses Festspielhaus --
Keywords: Concertos (Piano trio); Music; Orchestral music, Arranged; Music -- Venezuela; Venezuela; Internet videos